WHAT IS PROFIT? - Littleton, A. C. (The Accounting Review, 1928)
Abstract Three different groups of people have formulated definitions of the term profit. Each has its own point of view. Economists as a rule are interested, first, in explaining why the phenomenon of profit appears in society or why profits are tolerated and second, in deciding what it is that determines who shall receive the benefit of profits. Here profit is considered a social phenomenon associated with problems of the distribution of the proceeds of society's productive activities among factors responsible for that production. Courts have had to pass upon questions of what is profit in connection with income tax matters and dividend declarations or insolvencies. In the latter case, courts have been mainly interested in seeing that the capital fund is not paid out as dividends to the detriment of creditors of limited liability enterprises and consequently are likely to accept as profit available for dividend all of the proprietorship except the original contribution. In tax cases courts are mainly concerned in construing statutes and thus in passing upon the question of whether the matter at issue was or was not profit within the intention of the legislature and not whether the matter was or was not profit in fact. Businessmen, on the other hand, view profits mainly as a measure of accomplishment. They are, of course, interested in the profit legally available for dividends.